A Case Study about Startups' Software Development Practices: A Preliminary Result - Souza, Renata; Malta, Karla; Silva, Roselane; Masiero, Paulo Cesar; de Almeida, Eduardo Santana; Machado, Ivan (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Recently software startups have been the focus of intense research, especially in the Software Engineering community. However, we need more empirical evidence that addresses how software startups perform their software development practices. This paper presents a case study of software startups to understand their software development practices. We conducted a multiple case study in ten software startups, incubated in industrial environments at All Saints Bay Ecosystem. The case study consisted of questionnaires, semi-structured interviews, non-participative observations, and archiving data analyses covering software development practices. The preliminary results allowed us to build an initial industrial startup model capturing the software startups' practices and the relationship among them. Early-stage startups do not adopt any software development methodology in its completeness. Instead, they work focusing on speed-up software development and guide development based on consumers' feedback. The findings of this study is a preliminary result, which needs to be tested through other interviews with practitioners that work in other startups to validate the model at its current stage.